Permeability of the blood-brain barrier through the phases of ischaemic stroke and relation with clinical outcome: protocol for a systematic review - Helena Donato; Sara Bernardo-Castro; Lino Ferreira; João Sargento-Freitas (BMJ Open)
Introduction Ischaemic stroke is the most prevalent type of stroke and is characterised by a myriad of pathological events triggered by a vascular arterial occlusion. Disruption of the blood-brain barrier (BBB) is a key pathological event that may lead to fatal outcomes. However, it seems to follow a multiphasic pattern that has been associated with distinct biological substrates and possibly contrasting outcomes. Addressing the BBB permeability (BBBP) along the different phases of stroke through imaging techniques could lead to a better understanding of the disease, improved patient selection for specific treatments and development of new therapeutic modalities and delivery methods. This systematic review will aim to comprehensively summarise the existing evidence regarding the evolution of the BBBP values during the different phases of an acute ischaemic stroke and correlate this event with the clinical outcome of the patient.Methods and analysis We will conduct a computerised search on Medline, EMBASE, Cochrane Central Register of Controlled Trials, Scopus and Web of Science. In addition, grey literature and ClinicalTrials.gov will be scanned. We will include randomised controlled trials, cohort, cross-sectional and case-controlled studies on humans that quantitatively assess the BBBP in stroke. Retrieved studies will be independently reviewed by two authors and any discrepancies will be resolved by consensus or with a third reviewer. Reviewers will extract the data and assess the risk of bias of the selected studies. If possible, data will be combined in a quantitative meta-analysis following the guidelines provided by Cochrane Handbook for Systematic Reviews of Interventions. We will assess cumulative evidence using the Grading of Recommendations, Assessment, Development and Evaluation approach.Ethics and dissemination Ethical approval is not needed. All data used for this work are publicly available. The result obtained from this work will be published in a peer-reviewed journal and disseminated in relevant conferences.PROSPERO registration number CRD42019147314.